ANALYSIS THE IMAGERY OF FATHER IN SYLVIA PLATH’S POEMS : ‘DADDY’ & ‘THE COLOSSUS’ - Mita Permata Sari; Nurul Wahidah; Anisa Nur’Aini (Nusantara Hasana Journal, 2024)
This research analyzes the use of father imagery in Sylvia Plath's poems "Daddy" and "The Colossus," revealing how Plath depicts power, contradiction, and the complexity of her emotional relationship with her father through visual, auditory, and tactile imagery, reflecting deep personal trauma and turmoil. This study uses a qualitative method with a descriptive and interpretative approach. Data were collected through careful reading of the poems "Daddy" and "The Colossus," followed by an analysis of visual, auditory, and tactile imagery to uncover the meanings, symbolism, and emotional struggles that reflect Plath's relationship with her father. Based on the analysis of father imagery in Sylvia Plath's poems "Daddy" and "The Colossus," it was found that Plath uses visual, auditory, and tactile imagery to depict the power, brutality, and complexity of her emotional relationship with her father, Otto Plath, reflecting deep personal trauma and turmoil. The conclusion from the analysis of Sylvia Plath's poems "Daddy" and "The Colossus" shows the use of strong imagery to depict trauma and the complex relationship with her father, revealing themes of power, brutality, and emotional struggle, reflecting deep and significant personal experiences.